The Effect of Debt to Equity Ratio, Return on Assets, and Total Assets Turnover on Company Value: Study On Food and Beverage Sub-Sector Manufacturing Companies on The Indonesia Stock Exchange In 2016-2020 - Ardhana, Astrid; Karyatun, Subur; Digdowiseiso , Kumba (CV ODIS, 2023)
This study is intended to determine the effect of the ratio of Debt to Equity Ratio, Return on Assets, and Total Assets turnover on Company Value in food and beverage sub-sector manufacturing companies on the Indonesia Stock Exchange in 2016-2020. With the Purposive sampling method and the number of samples taken as many as 15 companies from the observation period of 5 consecutive years in food & beverage sector companies on the Indonesia Stock Exchange. Eviews 9 is the analytical tool used in this study. The result states that the Debt to debt-equity ratio is negative and insignificant to the Company's Value. Return On Assets has a positive and significant influence on Company Value as well and Total Assets turnover has a positive and significant effect on Company Value.